Analysis of Students' Mathematical Reasoning in Triangles by Learning Style Preferences - Rakha Pradestya; Sudirman Sudirman; Ardi Dwi Susandi (Journal of Instructional Mathematics, 2024)
This study analyzes students' mathematical reasoning abilities concerning triangles and special lines, considering their individual learning styles. The qualitative case study was conducted at Khalifah Boarding Junior High School, involving three grade VIII students representing visual, auditory, and kinesthetic learning styles. The selection of these students was based on their learning style preferences identified through a questionnaire. Data collection included mathematical ability tests and interviews, which were then analyzed by triangulating answer sheet observations and interview findings. Initial data revealed a distribution of 50% visual learners, 42% auditory learners, and 8% kinesthetic learners. Subjects were purposively selected based on the highest scores in each learning style group. The subjects demonstrated differences in understanding and approaching problem-solving, influenced by their learning styles. This study highlights specific challenges and recommendations for each subject, emphasizing the importance of a tailored learning approach to improve mathematical understanding and problem-solving skills. The research underscores the significance of recognizing and accommodating diverse learning styles to optimize students' academic achievements in mathematics.